2012
DOI: 10.1097/mcg.0b013e3182333820
|View full text |Cite
|
Sign up to set email alerts
|

Recent Safety Concerns With Proton Pump Inhibitors

Abstract: There have been recent concerns about the safety of proton pump inhibitors (PPIs). We focus here on 3 specific concerns-the possible interaction between PPIs and clopidogrel, the postulated link between PPI use and fractures, and the possibility that long-term PPI use might lead to hypomagnesemia. There is evidence for an in vitro interaction between clopidogrel and at least some PPIs. The Food and Drug Administration (FDA) has warned against the use of certain PPIs by patients on clopidogrel. However, a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
2
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 134 publications
(210 reference statements)
0
51
2
8
Order By: Relevance
“…As PPIs have become commonly 29 used for long-term maintenance, concerns have been raised about the safety of such use 6 . 30 Studies have showed that PPI use is associated with malabsorption of vitamins and 31 minerals 7,8 , an increased risk of infections, such as pneumonia 9 and enteric infection 10 , and 32 an increased fracture risk 11,12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As PPIs have become commonly 29 used for long-term maintenance, concerns have been raised about the safety of such use 6 . 30 Studies have showed that PPI use is associated with malabsorption of vitamins and 31 minerals 7,8 , an increased risk of infections, such as pneumonia 9 and enteric infection 10 , and 32 an increased fracture risk 11,12 .…”
mentioning
confidence: 99%
“…The importance of reducing any overuse of PPIs is not limited to the associated costs, but 28 also to the risks of taking the drugs on a long-term basis 6 . As PPIs have become commonly 29 used for long-term maintenance, concerns have been raised about the safety of such use 6 .…”
mentioning
confidence: 99%
“…Antacids may affect the absorption of other medications and should not be prescribed in individuals with decreased renal function due to the risk of accumulation of aluminum and magnesium [26]. Long term Proton pump inhibitor therapy should also be avoided as, according to recent reports, they are known to cause osteoporosis, vitamin B 12 deficiency, interact with clopidogrel among other effects [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Their main finding -that PPI co-therapy did not modify the protective effect of clopidogrel -is in keeping with our recent analyses of the literature. 2,3 Hopefully, their findings will go some way towards resolving the ongoing controversy about the use of PPIs by patients on clopidogrel.…”
Section: Ppi Co-therapy Did Not Adversely Affect Outcomes In Clopidogmentioning
confidence: 99%